Physiopathology and diagnosis of cardiotoxicity in patients submitted to chemotherapy treatment - Filipe C. Marmelo; Cátia F.R. Sá (Frontiers Media S.A., 2019)
Cardiovascular diseases and neoplastic diseases are the two main causes of morbidity and mortality in the world. Treated cancer patients usually develop cardiac diseases late in life due to chemotherapy-induced heart damage. The type of damage caused to the heart depends on the type of agent used during cancer treatment. It is expectable to observe ventricular impairment in patients treated with anthracyclines, while pyrimidines and some signalling inhibitors may damage the coronary circulation. Several techniques can be used to help diagnose early cardiac affections, such as biomarkers and auxiliary diagnostic tests. The information obtained can help physicians adjust chemotherapy doses, thus avoiding unnecessary heart damage. Although there is not yet a broad offer of cardioprotective drugs specific to these cases, some pharmacological agents used in common cardiology can also be applied here, such as beta-blockers and angiotensinogen-converting enzyme inhibitors.